Does the Experience of Being Phubbed by Friends Affect Psychological Well-Being? The Mediating Roles of Loneliness, Relationship Satisfaction, and Self-Esteem - Yeslam Al-Saggaf (Human Behavior and Emerging Technologies)
Phubbing is so common that many probably think it is harmless. Past research found that phubbing partners indirectly affected their well-being. The current study was aimed at investigating whether phubbing friends is also indirectly related to their well-being. A total of 457 smartphone users attempted an online survey from which 202 complete responses were included in the final analysis. The questionnaire contained measures of the experience of being phubbed by friends, psychological well-being, loneliness, friendship satisfaction, and self-esteem. A mediation analysis revealed a significant indirect effect of being phubbed by friends on psychological well-being, through the mediating roles of loneliness and relationship satisfaction and the sequential mediating roles of loneliness and self-esteem, and relationship satisfaction and self-esteem. Being phubbed by friends was associated with an increase in the phubbed friends’ levels of loneliness and a decrease in their levels of friendship satisfaction and, as a result, in a worsening of their psychological well-being. An increase in levels of loneliness or a decrease in levels of friendship satisfaction was also negatively associated with self-esteem and, in turn, with psychological well-being. These findings extend past research on partner phubbing by establishing new pathways between the experience of being phubbed by friends and psychological well-being. Overall, this study contributes important insights into friends’ use of smartphones in face-to-face settings by highlighting the psychological mechanism that explains the relationship between being phubbed by friends and the phubbed individuals’ psychological well-being.